2006
DOI: 10.1007/11847250_22
|View full text |Cite
|
Sign up to set email alerts
|

Random Separation: A New Method for Solving Fixed-Cardinality Optimization Problems

Abstract: We develop a new randomized method, random separation, for solving fixed-cardinality optimization problems on graphs, i.e., problems concerning solutions with exactly a fixed number k of elements (e.g., k vertices V) that optimize solution values (e.g., the number of edges covered by V). The key idea of the method is to partition the vertex set of a graph randomly into two disjoint sets to separate a solution from the rest of the graph into connected components, and then select appropriate components to form a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
114
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(115 citation statements)
references
References 14 publications
1
114
0
Order By: Relevance
“…Our algorithm is based on the random separation techniques introduced by Cai, Chan and Chan [8]. We complement this result by showing in Section 4 that Editing to a Graph of Given Degrees parameterized by k + d has no polynomial kernel unless NP ⊆ coNP /poly if {vertex deletion, edge addition} ⊆ S. This resolves an open problem by Mathieson and Szeider [17].…”
Section: Editing To a Graph Of Given Degreesmentioning
confidence: 68%
“…Our algorithm is based on the random separation techniques introduced by Cai, Chan and Chan [8]. We complement this result by showing in Section 4 that Editing to a Graph of Given Degrees parameterized by k + d has no polynomial kernel unless NP ⊆ coNP /poly if {vertex deletion, edge addition} ⊆ S. This resolves an open problem by Mathieson and Szeider [17].…”
Section: Editing To a Graph Of Given Degreesmentioning
confidence: 68%
“…It has previously been shown that, using random separation, DkS can be solved in 2 O(∆k) time with one-sided error and constant error probability [6]. Our algorithm above applied to DkS runs in 2 O(log(∆)k) time.…”
Section: Lemmamentioning
confidence: 99%
“…It is, however, fixed-parameter tractable with respect to the combined parameter "maximum degree ∆ and k" [6]. Holzapfel et al [13] showed that DkS remains NP-hard, even when looking only for subgraphs with average degree at least 2+Ω(1/k 1− ) for 0 < < 2.…”
Section: Introductionmentioning
confidence: 99%
“…Our FPT algorithm uses the following connection with a vertex cover problem that is solvable by the random separation method of Cai, Chan and Chan [4].…”
Section: Dual Connectedness By Vertex Deletionmentioning
confidence: 99%
“…By Lemma 3, it suffices to find k vertices in T that cover exactly 2k edges. We use a modification of the random separation algorithm of Cai, Chan and Chan [4] for finding a subset of vertices to cover exactly k edges.…”
Section: Theorem 3 Dually Connected Deletion Is Np-complete and W[1]mentioning
confidence: 99%